HIV Testing and Diagnosis Rates in Relation to HIV Indicator Conditions: A Multicenter Retrospective Analysis from Türkiye - Hatipoglu C. A.; ÜNAL S.; Koc M. M.; Aydogmus F. K.; Bayindir Y.; GENÇER S.; TAŞOVA Y.; DURDU B.; KUŞCU F.; Kayaaslan B.; et al. (My University, 2026)
Objective HIV testing procedure in the presence of HIV indicator conditions is considered an effective strategy to identify undiagnosed people living with HIV. We aimed in this study to evaluate HIV testing and diagnosis rates obtained via non-targeted testing in seven hospitals across T & uuml;rkiye, specifically focusing on patients with HIV indicator conditions.Objective HIV testing procedure in the presence of HIV indicator conditions is considered an effective strategy to identify undiagnosed people living with HIV. We aimed in this study to evaluate HIV testing and diagnosis rates obtained via non-targeted testing in seven hospitals across T & uuml;rkiye, specifically focusing on patients with HIV indicator conditions.Methods Data from a total of 3,371,188 patients with hospital admissions for various clinical conditions were analyzed in this retrospective multicenter cross-sectional study, which was carried out in seven hospitals within a 6-months period. HIV testing and HIV diagnosis rates were retrospectively evaluated in the overall population and in the subgroups of patients with and without HIV-indicator conditions.Methods Data from a total of 3,371,188 patients with hospital admissions for various clinical conditions were analyzed in this retrospective multicenter cross-sectional study, which was carried out in seven hospitals within a 6-months period. HIV testing and HIV diagnosis rates were retrospectively evaluated in the overall population and in the subgroups of patients with and without HIV-indicator conditions.Methods Data from a total of 3,371,188 patients with hospital admissions for various clinical conditions were analyzed in this retrospective multicenter cross-sectional study, which was carried out in seven hospitals within a 6-months period. HIV testing and HIV diagnosis rates were retrospectively evaluated in the overall population and in the subgroups of patients with and without HIV-indicator conditions.Results Rates of HIV testing and positivity in the overall population of 3,371,188 patients screened across seven hospitals were 8.3% (281,321/3,371,188) and 0.2% (557/281,321), respectively. HIV testing and HIV positivity rates in 19,410 patients with HIV-indicator conditions were 11.5% (2,225/19,410) and 0.4% (9/2,225), respectively. HIV testing and HIV positivity rates in 3,351,778 patients without HIV-indicator conditions were 8.3% (279,096/3,351,778) and 0.2% (548/279,096), respectively. The rate of HIV testing and HIV positivity in patients with HIV-indicator conditions was statistically significantly higher than in the patients without HIV-indicator conditions (p = 0.000 and p = 0.047, respectively).Results Rates of HIV testing and positivity in the overall population of 3,371,188 patients screened across seven hospitals were 8.3% (281,321/3,371,188) and 0.2% (557/281,321), respectively. HIV testing and HIV positivity rates in 19,410 patients with HIV-indicator conditions were 11.5% (2,225/19,410) and 0.4% (9/2,225), respectively. HIV testing and HIV positivity rates in 3,351,778 patients without HIV-indicator conditions were 8.3% (279,096/3,351,778) and 0.2% (548/279,096), respectively. The rate of HIV testing and HIV positivity in patients with HIV-indicator conditions was statistically significantly higher than in the patients without HIV-indicator conditions (p = 0.000 and p = 0.047, respectively).Results Rates of HIV testing and positivity in the overall population of 3,371,188 patients screened across seven hospitals were 8.3% (281,321/3,371,188) and 0.2% (557/281,321), respectively. HIV testing and HIV positivity rates in 19,410 patients with HIV-indicator conditions were 11.5% (2,225/19,410) and 0.4% (9/2,225), respectively. HIV testing and HIV positivity rates in 3,351,778 patients without HIV-indicator conditions were 8.3% (279,096/3,351,778) and 0.2% (548/279,096), respectively. The rate of HIV testing and HIV positivity in patients with HIV-indicator conditions was statistically significantly higher than in the patients without HIV-indicator conditions (p = 0.000 and p = 0.047, respectively).Results Rates of HIV testing and positivity in the overall population of 3,371,188 patients screened across seven hospitals were 8.3% (281,321/3,371,188) and 0.2% (557/281,321), respectively. HIV testing and HIV positivity rates in 19,410 patients with HIV-indicator conditions were 11.5% (2,225/19,410) and 0.4% (9/2,225), respectively. HIV testing and HIV positivity rates in 3,351,778 patients without HIV-indicator conditions were 8.3% (279,096/3,351,778) and 0.2% (548/279,096), respectively. The rate of HIV testing and HIV positivity in patients with HIV-indicator conditions was statistically significantly higher than in the patients without HIV-indicator conditions (p = 0.000 and p = 0.047, respectively).Discussion Our findings revealed that only 11.5% of patients with HIV-indicator conditions underwent HIV testing, indicating that most patients are not timely diagnosed despite having HIV-indicator conditions, and these patients remain at risk of living with unknown HIV status. The utilization of testing outside the HIV-indicator conditions criteria in 8.3% of cases was also notable. The likelihood of a positive diagnosis rate was at least 2-fold increased when the screening was guided by HIV-indicator conditions.Discussion Our findings revealed that only 11.5% of patients with HIV-indicator conditions underwent HIV testing, indicating that most patients are not timely diagnosed despite having HIV-indicator conditions, and these patients remain at risk of living with unknown HIV status. The utilization of testing outside the HIV-indicator conditions criteria in 8.3% of cases was also notable. The likelihood of a positive diagnosis rate was at least 2-fold increased when the screening was guided by HIV-indicator conditions.Discussion Our findings revealed that only 11.5% of patients with HIV-indicator conditions underwent HIV testing, indicating that most patients are not timely diagnosed despite having HIV-indicator conditions, and these patients remain at risk of living with unknown HIV status. The utilization of testing outside the HIV-indicator conditions criteria in 8.3% of cases was also notable. The likelihood of a positive diagnosis rate was at least 2-fold increased when the screening was guided by HIV-indicator conditions.Conclusion In conclusion, according to the study, HIV testing in patients with HIV-indicator conditions increased the rate of HIV diagnosis, but the rate of requesting testing in the presence of HIV-indicator conditions was low. HIV testing practices among physicians in the Turkish healthcare settings should be improved with interventions for an improved awareness of HIV-indicator conditions-guided HIV testing, and adopting the related guidelines to appropriately identify undiagnosed HIV cases.Conclusion In conclusion, according to the study, HIV testing in patients with HIV-indicator conditions increased the rate of HIV diagnosis, but the rate of requesting testing in the presence of HIV-indicator conditions was low. HIV testing practices among physicians in the Turkish healthcare settings should be improved with interventions for an improved awareness of HIV-indicator conditions-guided HIV testing, and adopting the related guidelines to appropriately identify undiagnosed HIV cases.
Keywords: Tıp; Mikrobiyoloji ve Klinik Mikrobiyoloji; Viroloji; Yaşam Bilimleri; Sağlık Bilimleri; Temel Tıp Bilimleri; Temel Bilimler; Medicine; Microbiology and Clinical Microbiology; Virology; Life Sciences; Health Sciences; Fundamental Medical Sciences; Natural Sciences; İmmünoloji; Yaşam Bilimleri (Life); Bulaşıcı Hastalıklar; Immunology; Life Sciences (Life); Infectious Diseases; Bulaşıcı hastalıklar; Genel İmmünoloji ve Mikrobiyoloji; General Immunology and Microbiology